The Effect of Reflective Journal Authentic Assessment on Students’ Writing Competence and Motivation - Jojor Siahaan; Maria Teodora Ping; Aridah Aridah; Yuni Utami Asih (Educational Studies: Conference Series, 2021)
Several studies on Reflective Journal Writing (RJW) have highlighted the positive learning experiences either in writing skills or writing competence. However, most of them were for adult students. This study aimed to see it in high school students as demanded in the syllabus 2013. The respondents were 70 from the 360 population by using simple random sampling. A Mix-method approach answered the research questions with the writing competence, questionnaire, and interview instruments. The treatment group got the reflective journal writing while the control group without reflective journal writing six times. Pretest applied before the treatment and posttest after treatment and followed with a questionnaire and an interview. The data analysis used two-way manova, paired sample t-test, independent t-test, and Interview. The effect size shown in Eta Square for motivation was 86.4% or 0.864 categorized large effect and for writing 9.6% or 0.096 categorized moderate effect. RJW had a significant simultaneous effect on students’ writing competence and motivation. The correlation of students’ writing partially was .527. It was bigger than .05. RJW had a partial effect on students’ writing competence. For motivation, the significance value was 7.488 meant that RJW had a partial effect. It supported with Qual analysis that showed on students’ willingness, desires of doing something, fun activity, enjoyment activity, satisfaction, and effort of facing problems. In conclusion, RJW was significant to increase or improve either students’ writing competence or motivation.